Hemodialysis during cardiopulmonary resuscitation in patients with severe metabolic acidosis. Issue 8 (August 2018) - Sahutoglu, Tuncay; Sahutoglu, Elif
Background/Aims: Severe metabolic acidosis during cardiopulmonary resuscitation is an important and yet unresolved issue. The potential use of hemodialysis for severe metabolic acidosis during cardiopulmonary resuscitation was investigated. Methods: Acute hemodialyses between January 2012 and April 2017 were reviewed for patients with concomitant hemodialysis and cardiopulmonary resuscitation. In addition, MEDLINE was searched for similar reports. Data were extracted from hospital records. Results: Two patients (36M, 70F) were found to study, without similar reports in MEDLINE. Cardiac arrests (in-hospital) occurred due to severe metabolic acidosis in both patients (due to ethylene glycol and metformin intoxications, respectively). Return of spontaneous circulation could not be obtained within the first 28 and 30 min of cardiopulmonary resuscitation only, whereas both patients had return of spontaneous circulation following at least 45 min of concomitant hemodialysis and cardiopulmonary resuscitation. One patient (70F) was discharged with good neurological outcome, but the other died. Conclusion: The addition of high-efficiency hemodialysis during cardiopulmonary resuscitation may contribute to the return of spontaneous circulation in patients with severe metabolic acidosis due to intoxication.